2010
DOI: 10.1377/hlthaff.2009.0521
|View full text |Cite
|
Sign up to set email alerts
|

New State Strategies To Meet Long-Term Care Needs

Abstract: Consumer-directed long-term care service programs give participants the flexibility they want, while reducing unmet need for home and community-based services and supports. States' efforts to expand such programs under Medicaid, including those supported by federal Cash and Counseling demonstration and evaluation grants, are often hindered by challenges related to costs, staffing and organizational issues, new infrastructure requirements, and resistance from stakeholders. Yet states have developed a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 2 publications
(2 reference statements)
0
31
0
Order By: Relevance
“…Additionally, although finding and targeting ideological champions to sell rebalancing efforts to their peers, as suggested by Doty et al (2010) is one strategy to improve policy implementation, it may be more fruitful to undertake more targeted research to ascertain where professionals are stuck in the implementation process and how to most effectively and efficiently move forward in ways that foster professional investment in rebalancing. Experts at the National Center for Participant-Directed Services have identified primary inhibitors to expanding participant-directed services at the state and local levels as lack of understanding and knowledge, lack of participation by those implementing change in developing the change, and absence of leadership buy-in (Gerhard, Sanders, & Sciegaj, 2010).…”
Section: Lessons For On-going Implementation Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, although finding and targeting ideological champions to sell rebalancing efforts to their peers, as suggested by Doty et al (2010) is one strategy to improve policy implementation, it may be more fruitful to undertake more targeted research to ascertain where professionals are stuck in the implementation process and how to most effectively and efficiently move forward in ways that foster professional investment in rebalancing. Experts at the National Center for Participant-Directed Services have identified primary inhibitors to expanding participant-directed services at the state and local levels as lack of understanding and knowledge, lack of participation by those implementing change in developing the change, and absence of leadership buy-in (Gerhard, Sanders, & Sciegaj, 2010).…”
Section: Lessons For On-going Implementation Effortsmentioning
confidence: 99%
“…Reflections by leaders of Medicaid's Cash & Counseling demonstration program (a precursor to NFI HCBS initiatives and aimed at testing consumer-directed HBCS models), suggested that the actions of individual administrators and practice professionals who championed the Cash & Counseling program helped lower resistance to shifting in service delivery models (Doty, Mahoney & Sciegaj, 2010). This champion model seems to indicate that shifting beliefs and perceptions of individual professionals play an important role in moving forward systems change.…”
Section: Introductionmentioning
confidence: 99%
“…268 Research from the programs in New Jersey, Arkansas, and Florida suggests that consumers' control over personal care greatly improves their satisfaction with care arrangements and their outlook on life, 269,270 and that it is a viable model for people with serious mental illnesses. 271 Summary and Implications Consumer-directed care is an important component of patient-centered care and can promote engagement and satisfaction among service users.…”
Section: Financing Services To Promote Consumer Choicementioning
confidence: 99%
“…On the policy side, state policymakers have been reluctant to allow family members to be paid caregivers, especially those residing in the same household as the program participant. This reluctance stems, in part, from concerns about the substitution of paid for unpaid care (Doty, Mahoney, & Sciegaj, 2010).…”
Section: Introductionmentioning
confidence: 99%